KANDUNGAN LOGAM BERAT TIMBAL, TEMBAGA, DAN ARSEN PADA SEDIMEN DI BENDUNGAN LOMAYA DAN BENDUNGAN ALOPOHU - Asiari, Mohamad Zikra; Nurmi, Nurmi; Jamin, Fitriah S.; Azis, Muhammad A. (Soil and Environment Journal, 2022)
HEAVY METAL CONTENTS OF Pb, Cu, AND As IN SEDIMENTS OF LOMAYA AND ALOPOHU DAMS This research determined heavy metal level of lead (Pb), Copper (Cu), and Arsenic (As) content in the sediment at Lomaya and Alopohu dams. Lomaya Dam located at Bolango Ulu Sub-district, District of Bone Bolango and Alopohu Dam at Dungalio Sub-district, district of Gorontalo. Sediment samples of Lomaya was taken at point of N 00037â€™70,6â€ E 123004â€™96â€, while that of Alopohu dam was taken at the coordinate of N 00033â€™29.5â€ E 122053â€™38.6â€. This research was conducted from April to May 2016. It reveals that the samples from both dams were contaminated with heavy metals of Pb, Cu, and As. The levels of heavy metals in Lomaya were 4,226 mg Pb/kg sediment, 1.225 mg Cu/kg sediment, and 0.148 mg As/kg sediment. Heavy metals in Alopohu dam were 4.198 mg Pb/kg, 4.225 mg Cu /kg, and 0.227 mg As/kg). The level of these three heavy metals both in Lomaya and Alopohu dams were below the allowed limit (Pb >30 mg/kg, Cu >65 mg/kg dan As >75 mg/kg). The statistical test of t test showed that the Pb level was not significantly differ from Cu level, but it was significantly different from the As level. In addition the Cu level did not significantly differ from the As level in both dams.